Penerapan Model Project Based Learning untuk Meningkatkan Nilai Karakter Kemandirian Siswa pada Mata Pelajaran IPS di Masa Pandemi Covid-19 - Herawati, Winda; Kurnia, Dadang; Aeni, Ani Nur (Jurnal Pena Ilmiah, 2021)
This study aims to determine, planning, implementing, obstacles, and student learning outcomes after applying the project based learning model to increase the value of student independence character values in social studies subjects during the covid-19 pandemic. This research is an action research with a level 3 action research design. This study uses a qualitative approach. Sources of data obtained from the results of observations, interviews, results of documentation, results of focus group discussions, and test results. The results of this study include: 1. In planning a project based learning model, you must first prepare a learning implementation plan that is in accordance with the characteristics of the model, 2. The implementation of the project based learning model must be adjusted to the steps contained in the learning implementation plan that has been made, 3. One of the obstacles to the project-based learning model is that students are constrained by internet quotas, 4. Student learning outcomes and independence increased after the project-based learning model was applied. The conclusion of this study is to show that the project based learning modei can increase the value of the independence character of students.